Evaluation of different temperature winter fodder species (Festulolium hybrids, dactylis species, lolium hybrids) and grass-legume mixtures in the warmer summer rainfall areas of South Africa - Kabine, Ezekiel Simon (University of Limpopo, 2016)
South Africa is regarded as a semi-arid area; only 28% of the country receives more than 600 mm rainfall recorded annually. Sustainable utilization of cool season fodder grasses in summer rainfall areas to produce winter animal feed remains a major problem. Farmers are affected by a shortage of adequate, good quality herbage for livestock during winter and dry periods on commercial farms. The study aimed to evaluate and compare the production potential of six Festulolium hybrids, three Dactylis species, and five Lolium hybrids and three grass-legume mixtures in the summer rainfall area. A total of 17 cultivars were evaluated for their DM production under the treatment of different fertilizer levels on three planting dates (16 March 2011, 21 April 2011 and 4 April 2012). The study was carried out at Hygrotech Seed Company (Experimental site), Dewagensdrift in Moloto Village outside Pretoria in the Gauteng Province. Data was collected on a monthly basis from sub-plots of 1 m x 1 m (m2) in 51 plots of 1.5 m x 6 m (9 m2), with nine rows that were 10 cm apart arranged under RCBD with three replicates per cultivar. Harvested fresh samples were taken, weighed, dried at 60ºC until they reached a constant dry weight and weighed to determine DM content. A Fischer’s protected LSD at the 5 % level was performed to compare the treatment means. Over a period of three years of study, it shows that the low fertilizer level resulted in the lowest DM production, with no significant difference occurring between medium and high fertilizer levels. To achieve optimum DM production with minimum cost medium fertilizer is recommended. The cultivars responded differently to the three different planting dates. The time of planting had an effect on DM production in winter. It is recommended that Festulolium hybrids and Lolium hybrids be planted earlier (March) for better DM production in winter.
Thesis (MSc. (Pasture Science)) -- University of Limpopo, 2016
Keywords: Annual ryegrass; Dry matter production; Perennial grass; Grass fertilizers; Temperature; Pastures -- South Africa